Experimental Study On The Impact Of DBD Plasma Actuator Geometry And Electrical Input On Thrust Generation - Rosli, Muhammad Farid Amirul (Universiti Sains Malaysia, 2022)
Dielectric Barrier Discharge (DBD) plasma actuator has established itself as a well-known device for flow control in aerodynamics. Because of its special qualities, the DBD plasma actuator has been employed in a large variety of studies. As an example, the DBD plasma actuator is a promising device with no moving components that ionises flow streams quickly, is flexible, and has an astonishingly low mass. DBD plasma actuators have been employed for many flow control applications, including flow control on airfoils, flow control around cylinders or bluff bodies, and enhancing aerodynamic performance, particularly in the automotive industry. A primary goal of this study is to introduce and experimentally investigated the DBD plasma actuator as an active flow control device since this device is well known for its capability for delaying flow separation by inducing thrust. This research focused on the evaluation of the impact of DBD plasma actuator geometry and electrical input on thrust generation , both for each design variable and their interactions. The effects of applied voltage, dielectric thickness and dielectric gap are each examined . The experimental model used in this research involves the use of the self-made actuators and for the measurement of the thrust was conducted by using direct thrust measurement consisting of a high precision electronic force balance. In this context, the thrust generated by the actuator is used as the performance measure for this research. It was discovered that the thickness of the dielectric material influenced the thrust produced by every recorded actuator. Even when provided with a high applied voltage, actuators made with a thick dielectric layer comprised of 6 layers of Kapton have difficulties creating plasma production. In addition, electrode gap was also seeming to be the primary contributor to zero thrust readings, especially in thick dielectric thickness. The actuator designed with a 1mm electrode gap or 6 layers of dielectric thickness results in a low thrust value, and in some instances, a thrust value reading of zero. This demonstrates that a negative interaction exists between the thick dielectric layer and the widened electrode gap. This implies that the actuator was successfully operated for thrust production on the thin dielectric layer with zero electrode gap, regardless of the applied voltage value.